(untitled) (Global Journal of Computer Science and Technology, 2014)
An approach is proposed that can be used to make these arch adaptive according to each user2019;s need using ontology .Our approach is distinct because it allows each user to perform more fine-grained search by capturing changes of each user2019;s preferences without any user effort. Such a method is not performed in typical search engines.